2018
DOI: 10.1002/jaal.723
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful and Expansive: Literacy Learning Through Technology‐Mediated Productions

Abstract: Most people have struggled with reading in one situation or another, depending on their appreciation for the content, their prior experiences, and the texts. This department column shares ways for educators to help literacy learners unlock their potential with instruction anchored in their skills, knowledge, ways of learning, interests, and attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Within media literacy education, efforts to teach for savvy consumption of information are well represented, as are efforts to teach youth to express their voices through dialogue, circulation and production (Crampton, Scharber, Lewis & Majors, 2018;Hobbs, 2010;Kahne et al, 2016;Middaugh & Evans, 2018). These elements are also discussed side-by-side as components of an overarching set of practices that make up media literacy.…”
Section: The Circulation and The Ethics Of Sharing In Civic Media Litmentioning
confidence: 99%
See 1 more Smart Citation
“…Within media literacy education, efforts to teach for savvy consumption of information are well represented, as are efforts to teach youth to express their voices through dialogue, circulation and production (Crampton, Scharber, Lewis & Majors, 2018;Hobbs, 2010;Kahne et al, 2016;Middaugh & Evans, 2018). These elements are also discussed side-by-side as components of an overarching set of practices that make up media literacy.…”
Section: The Circulation and The Ethics Of Sharing In Civic Media Litmentioning
confidence: 99%
“…These elements are also discussed side-by-side as components of an overarching set of practices that make up media literacy. However, concerns about misinformation are usually confined to analysis of youth involved in the explicit task of assessing credibility (Kahne & Bowyer, 2017;Martens & Hobbs, 2015) and sometimes in relation to production of media (Crampton et al, 2018;Hobbs, 2010;Garcia, Mirra, Morrell, Martinez, & Scorza, 2015), but not systematically discussed in relation to the circulation of media.…”
Section: The Circulation and The Ethics Of Sharing In Civic Media Litmentioning
confidence: 99%
“…Crampton et al. () also discovered that urban adolescents’ experiences with a digital literacy project “resulted in changes in thought, perspective, and identity” (p. 576) and that the technology tools allowed for experiences of exchange (and collaboration) and had a significant impact on student learning. These findings are consistent with those from Karam's () case study of an Iraqi refugee adolescent who was resistant to school‐based literacy practices until the opportunity to create an online game (as an alternative assignment) allowed him to “present new identities and seek new possibilities of selfhood” (p. 516) that resonated with his out‐of‐school identity as an expert gamer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Johnson () argued for a shift in how the field views success to encompass the complex ways in which African American youths in particular experience education. The growing number of studies that have demonstrated how urban youths use and reappropriate technology to create meaningful work represents such a counternarrative (e.g., Crampton, Scharber, Lewis, & Majors, ; Lewis Ellison, ; Shapiro & MacDonald, ).…”
mentioning
confidence: 99%
“…There has been emerging attention given to teaching youth to search for and assess the credibility of online media (McGrew et al , 2018), as well as produce their own (Crampton et al , 2018). Yet, there has been limited research surrounding the most common online form of civic engagement in the digital age – the circulation of social media within online social networks (Cohen and Kahne, 2012; Jenkins et al , 2016; Middaugh, 2018).…”
Section: Introductionmentioning
confidence: 99%